The Influence of Social Media on the Promotion and Distribution of Digital Publishing Products in Library Services - Dea Azalia Ramadhani; Annissa Dinanda; Zafirah Hadinah Khalisah; Fitria Azahra; Nazwa Sakinah Nst (UIN Raden Intan Lampung, 2026)
The development of information and communication technology has significantly transformed library service systems, particularly in the promotion and distribution of digital publishing products. Libraries increasingly utilize social media as a medium for communication, service promotion, and digital information dissemination to the public. This study aims to analyze the influence of social media on the promotion and distribution of digital publishing products in library services. The research method employed is a Systematic Literature Review (SLR), which reviews various scientific articles obtained from Google Scholar and SINTA-indexed journals published between 2016 and 2025. The research process was conducted through four stages: identification, selection, analysis, and interpretation of relevant articles. The results indicate that social media has a significant influence on the effectiveness of library promotion and the distribution of digital publishing products, such as e-books, e-journals, institutional repositories, and other digital information services. Social media platforms, including Instagram, Facebook, WhatsApp, and YouTube, are found to be effective in increasing interaction between libraries and users, expanding information reach, and enhancing user interest in utilizing digital library services. However, several challenges remain in implementation, including limited human resources, inconsistent content management, and low levels of digital innovation in libraries. Therefore, libraries need to develop more creative and sustainable digital promotion strategies to optimize the use of social media in supporting library services.